Glycolipid antigen recognition by invariant natural killer T cells and its role in homeostasis and antimicrobial responses - Hayashizaki, Koji; Kamii, Yasuhiro; Kinjo, Yuki (Frontiers in Immunology, 2024)
Due to the COVID-19 pandemic, the importance of developing effective vaccines has received more attention than ever before. To maximize the effects of vaccines, it is important to select adjuvants that induce strong and rapid innate and acquired immune responses. Invariant natural killer T (iNKT) cells, which constitute a small population among lymphocytes, bypass the innate and acquired immune systems through the rapid production of cytokines after glycolipid recognition; hence, their activation could be used as a vaccine strategy against emerging infectious diseases. Additionally, the diverse functions of iNKT cells, including enhancing antibody production, are becoming more understood in recent years. In this review, we briefly describe the functional subset of iNKT cells and introduce the glycolipid antigens recognized by them. Furthermore, we also introduce novel vaccine development taking advantages of iNKT cell activation against infectious diseases.